2021
DOI: 10.1002/ppul.25335
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of asthma exacerbation in children during the coronavirus disease pandemic with strict mitigative countermeasures

Abstract: Background: Strict countermeasures for coronavirus disease (COVID-19) were undertaken in China without knowing their influence on asthma.Objective: To investigate the associations between the frequencies of asthma exacerbations and respiratory infections and air pollutants before and during the COVID-19 pandemic, which were direct consequences of countermeasures undertaken for the pandemic.Methods: Asthma exacerbations and respiratory infections among hospitalized children in the permanent population of Guangz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…The main characteristics of the 10 articles were summarized in Table 1. AHRQ scores suggested that all studies scored at 8–9 as high quality 14 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main characteristics of the 10 articles were summarized in Table 1. AHRQ scores suggested that all studies scored at 8–9 as high quality 14 …”
Section: Resultsmentioning
confidence: 99%
“…Ten studies, [14][15][16][17][18][19][20][21][22][23] with 22,159 subjects were included for the final meta-analysis. The sample size of the studies ranged from 16 to 18,912.…”
Section: Study Characteristicmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors recently discussed the potential factors involved in the decline in pediatric asthma exacerbations during lockdown, 37 including improved air quality levels; however, a relevant role of the fall in the concentration of air pollutants still has to be demonstrated. Recently, also Fan et al, 38 for example, failed to demonstrate such a direct correlation.…”
Section: Discussionmentioning
confidence: 97%
“…Other authors recently discussed the potential factors involved in the decline in pediatric asthma exacerbations during lockdown,37 including improved air quality levels; however, a relevant role of the fall in the concentration of air pollutants still has to be demonstrated. Recently, also Fan et al,38 for example, failed to demonstrate such a direct correlation. Pollen emissions, which are not impacted by changes in human behaviors and social restrictions, did not present substantial variations beyond their interannual variability during lockdown periods.…”
mentioning
confidence: 97%